Detection of Non‐Metallic Inclusions in Quenched and Tempered Steel Bars by XCT and after Fatigue Life Testing. Issue 3 (21st July 2015) - Gusenbauer, Christian; Reiter, Michael; Kastner, Johann; Kloesch, Gerald
Abstract : Non‐metallic inclusions (NMIs) determine to a high degree the quality and cleanness of steel and are often the reason for functional failure, especially in dynamic‐stressed components. Therefore, it is important to have accurate, fast, and reliable characterization methods for these unwanted material inhomogeneities. In this paper, two different methods for the detection of NMIs are compared: X‐ray‐computed tomography (XCT) and fatigue life testing. XCT allows the detection and analysis of material inhomogeneities and their positions in a 3D volume. The evaluation of XCT‐data of Fe‐based materials can be rather difficult, since the results are usually prone to image noise, offer poor contrast, and the interpretation is affected by artifacts. Suitable evaluation strategies for detection and classification are presented. The degradation of steel samples by dynamic fatigue testing is a destructive way of determining the existence of harmful NMIs. If there is an NMI of critical size in the sample, a functional failure may occur. The fracture surface is investigated by scanning electron microscopy (SEM), equipped with an energy dispersive X‐ray (EDX) spectroscopy unit in order to identify shape, type, and chemical composition of the harmful NMI. Abstract : This paper deals with the production, detection, and identification of harmful NMIs in steel bars by means of XCT and fatigue life testing and the subsequent inspection of the resulting fracture surface by SEM and EDX. These characterization methods enable NMI design by modifying its chemical composition during secondary metallurgical processing and thus improving steel cleanness.